2006
DOI: 10.1158/1078-0432.ccr-05-2136
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Reverse Transcription-PCR Quantification of Cytokeratin mRNA in the Detection of Sentinel Lymph Node Invasion in Oral and Oropharyngeal Squamous Cell Carcinoma: A Comparison with Immunohistochemistry

Abstract: Purpose:The main goal of sentinel lymph node (SLN) detection in head and neck squamous cell carcinomas is to limit neck dissections to pN+ cases only. However, intraoperative + diagnosis cannot be routinely done using the current gold standard, serial step sectioning with immunohistochemistry. Real-time quantitative reverse transcription-PCR (RT-PCR) is potentially compatible with intraoperative use, proving highly sensitive in detecting molecular markers. This study postoperatively assessed the accuracy of qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…Detection of metastases using molecular markers has been reported previously (Roepman et al 2005). However, there is still a need for additional sensitive markers to detect individual DTCs themselves in diVerent specimens (Garrel et al 2006). The Wrst step in identifying those candidates is to determine which genes are frequently and strongly expressed in primary site of OSCC by high-density cDNA microarrays allowing the investigation of a large number at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of metastases using molecular markers has been reported previously (Roepman et al 2005). However, there is still a need for additional sensitive markers to detect individual DTCs themselves in diVerent specimens (Garrel et al 2006). The Wrst step in identifying those candidates is to determine which genes are frequently and strongly expressed in primary site of OSCC by high-density cDNA microarrays allowing the investigation of a large number at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Single frozen sections can be obtained intra-operatively, but also show a suboptimal sensitivity of between 50% and 85% 6 7. Therefore, one-step nucleic acid amplification (OSNA) has recently been introduced for breast cancer using cytokeratin 19 (CK19), and various authors have reported that OSNA assay8–10 can detect lymph node metastasis as accurately as conventional pathology, allowing immediate diagnosis of lymph node metastasis and eliminating the need for pathological evaluation during surgery.…”
mentioning
confidence: 99%
“…Indeed, this rapid technique seems to be a valuable tool for the detection of lymph node invasion of breast adenocarcinomas (Kataoka et al, 2000), skin melanomas (Blaheta et al, 2001), and HNSCC (Hamakawa et al, 2000(Hamakawa et al, , 2004Becker et al, 2004;Shores et al, 2004). We have previously shown that CK17 mRNA quantification could accurately determine sentinel node staging (Garrel et al, 2006). However, this marker did not permit the detection of MIs sized o450 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, real-time reverse transcriptase-PCR (RT -PCR) may be helpful because it is operator independent and, with some adaptation, can be automated and rapidly performed (Raja et al, 2002;Hamakawa et al, 2004). In a previous study, we demonstrated that cytokeratin (CK)17 mRNA quantification could be evaluated in SLNs by semiquantitative RT -PCR and that neck staging could be performed with relevant sensitivity and specificity when compared with SS-IHC staging (Garrel et al, 2006). However, minute micrometastases (MIs) sized o450 mm produced signals similar to those of negative SLN controls and were thus undiagnosed by CK17 mRNA level quantification, showing the limitation of this mRNA marker for the detection of metastases in SLNs.…”
mentioning
confidence: 99%